Kingdom of Lesotho : 2015 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
The 2015 Article IV Consultation discusses key issues related to the economic growth of Lesotho. Although Lesotho achieved solid economic growth with only moderate inflation in the several years, this growth has failed to reduce poverty in the country. Lesotho's major chunk of revenue comes from South African Customs Union to finance large government expenditures, but this revenue will fall sharply in fiscal year 2016/17. Despite having substantial international reserves and fiscal buffers, a major fiscal adjustment over the next two to three years will be needed to maintain macroeconomic stability. The private sector needs to be the engine for job creation to strengthen inclusiveness.